Key performance indicators: developing, implementing, and using winning KPIs - Parmenter, David
Praise for Key Performance Indicators: Developing, Implementing, and Using Winning KPIs "Developing the right KPIs is a problem for most organizations. David Parmenters insightful approach offers a practical guide that will help managers to overcome these problems and turn concepts into reality in a timely way. ?Jeremy Hope, cofounder and Director of the Beyond Budgeting Round Table, and author of Reinventing the CFO Many organizations have struggled to match their balanced scorecard vision with actual implementation success. This book may well be the missing link. By distilling the process into twelve logical steps and by providing checklists and worksheets for each step, David Parmenter reduces the whole endeavor into attainable proportions. He also helps instill the confidence that senior leaders and managers need to both take on the task and see it to fruition." ?Sam Sheikh, Editor, Scorecard and Performance Management, BetterManagement.com "This is a must-read book for all senior managers. The correct selection and deployment of performance measures is essential to ensure that all resources and effort are focused on achieving business strategy . . . and yet so many organizations select the wrong performance measures. This is a straightforward and practical book that clearly explains what 'key performance indicators are and how they should be used as part of an integrated performance improvement strategy.